Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Novel symbioses between reef fishes and serpulid polychaetes in the Caribbean Sea - Morgan F. Bennett-Smith; Elizabeth McNamee; Samantha Masih; Timothy Lis; Mason Murchison; Allison Cinelli; Toshith Bhaumik; Catheline Y. M. Froehlich; Anna DeLoach; Ned DeLoach; Ninon Martinez; Peter M. Buston; et al. (Symbiosis, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Self-cover cropping systems and the plusquam-annual: New tools for cropping system sustainability - Virginia Nichols; Prabin Bajgain; Laura Dixon; Kim Henrik Hebelstrup; Claus Krogh Madsen; Robin Morgan; Valentin Picasso (Agricultural Systems, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Grassland Bird Species Decline With Colonial‐Era Landscape Change in a Tropical Montane Ecosystem - Vijay Ramesh; Priyanka Hariharan; Pratik Rajan Gupte; Ashwini V. Mohan; V. A. Akshay; Amrutha Rajan; Chandrasekar Das; Ian Lockwood; V. V. Robin; Morgan W. Tingley; Ruth DeFries (Global Change Biology, 2025)
The impacts of colonial‐era ecosystem changes on tropical biodiversity are poorly understood. We analyzed a 170‐year dataset on land cover and bird observations in an Old World tropical montane landscape in the Western Ghats, India, to determine if and how historical landscape changes have impacted 85 bird species. A comparison of historical land cover and classified satellite imagery (1848–2018) revealed approximately an 80% decrease in grassland area and a concomitant increase in tea and timber plantations stemming from colonial‐era policies and associated legacies of large‐scale planting of cash crops and exotic woody species. We found that relative species abundances of about 90% of grassland birds have significantly declined while around 53% of forest bird species remained stable or even increased in relative abundance over the same period. Over 74% of generalist bird species have become more common over the same period, possibly due to reduced habitat specialization. Our findings show that colonial‐era policies, continued postindependence, of tree planting across open natural ecosystems have resulted in severe loss of grassland habitats and a concomitant decline in the relative abundance of grassland bird species.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

A multi-approach study to reveal eel life-history traits in an obstructed catchment before dam removal - Nils Teichert; Anne Lizé; Hélène Tabouret; Claudia Gérard; Gilles Bareille; Anthony Acou; Alexandre Carpentier; Thomas Trancart; Laure-Sarah Virag; Emma Robin; Morgan Druet; Jordan Prod’Homme; et al. (Hydrobiologia, 2022)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Effects of Elevated CO2 on the Swainsonine Chemotypes of Astragalus lentiginosus and Astragalus mollissimus - Daniel Cook; Dale R. Gardner; James A. Pfister; Clinton A. Stonecipher; Joseph G. Robins; Jack A. Morgan (Journal of Chemical Ecology, 2017)

Taking High Conservation Value from Forests to Freshwaters - Robin Abell; Siân K. Morgan; Alexis J. Morgan (Environmental Management, 2015)

Impact of precipitation dynamics on net ecosystem productivity - William Parton; Jack Morgan; David Smith; Stephen Del Grosso; Lara Prihodko; Dan LeCain; Robin Kelly; Susan Lutz (Global Change Biology, 2012)
Net ecosystem productivity ( NEP ) was measured on shortgrass steppe ( SGS ) vegetation at the USDA C entral P lains E xperimental R ange in northeastern C olorado from 2001 to 2003. Large year‐to‐year differences were observed in annual NEP , with >95% of the net carbon uptake occurring during M ay and J une. Low precipitation during the 2002 A pril to J une time period greatly reduced annual net carbon uptake. Large precipitation events (>10 mm day −1 ) promoted carbon uptake, while small precipitation events ( −1 ) enhanced heterotrophic respiration and resulted in a net loss of carbon from the system. Large precipitation event enhanced carbon uptake was attributed to increased soil water content ( SWC ), which promotes plant photosynthesis. The large precipitation events which occurred from J uly to O ctober have lower increases in daytime net CO 2 uptake ( NEP d ) due to the presence of low live plant biomass compared to earlier in the growing season. Live aboveground plant biomass ( AGB ), solar radiation, and SWC were the major variables that controlled NEP d , while AGB , SWC , and relative humidity control nighttime respiration losses ( NEP n ). Aboveground plant biomass is the most important variable for controlling both NEP d and NEP n dynamics. These results suggest that the major factor controlling growing season NEP n is the amount of carbon fixed via photosynthesis during the day. Heterotrophic soil respiration is greatly enhanced for one to 2 days following rainfall events with daily rainfall events >5 mm having a similar increase in respiration (>3.00 g m Cm −2 day −1 ). In addition, the size of the heterotrophic respiration pulse is independent of both the amount of time since the last rainfall event and the time of occurrence during the growing season.

Antibiotic and Disinfectant Susceptibility Profiles of Vancomycin-Resistant Enterococcus faecium (VRE) Isolated from Community Wastewater in Texas - Ross C. Beier; Sara E. Duke; Richard L. Ziprin; Roger B. Harvey; Michael E. Hume; Toni L. Poole; H. Morgan Scott; Linda D. Highfield; Walid Q. Alali; Kathleen Andrews; Robin C. Anderson; David J. Nisbet (Bulletin of Environmental Contamination and Toxicology, 2008)

Influence of nursery soil amendments on water relations, root architectural development, and field performance of Douglas-fir transplants - Douglass F. Jacobs; Robin Rose; Diane L. Haase; Paul D. Morgan (New Forests, 2003)